Macro-Economic Models for R&D and Innovation Policies - Francesco Di Comite; d'Artis Kancs (European Commission, Joint Research Centre (JRC), 2015)
This report compares R&D modelling approaches in four macroeconomic models used by the European Commission for ex-ante policy impact assessment: one Dynamic Stochastic General Equilibrium (DSGE) model – QUEST; one Spatial Computable General Equilibrium (SCGE) model – RHOMOLO; one Computable General Equilibrium (CGE) model – GEM-E3; and one macro-econometric model – NEMESIS. The report critically compares particularly those parts of the four models that are relevant to R&D transmission mechanisms and interfaces for implementing policy shocks. Given that R&D investment decisions are inherently dynamic, QUEST appears to be the most suitable model for assessing the impact of R&D and innovation policies over time, as it is the only model with inter-temporal optimisation of economic agents. In order to address questions related to geographic concentration of innovative activities and spatial knowledge spillovers, RHOMOLO has a comparative advantage, as it is the only one which models regional economies and spatial interactions between them explicitly. Due to its detailed treatment of energy sectors and environmental issues, GEM-E3 appears to be the most suitable model for assessing the impact of innovation in clean energy. For a more detailed modelling of different types of innovation measures, NEMESIS can provide valuable insights thanks to its richness in estimating and accounting for specific channels of innovation. We also identify avenues for future research, which in our view could improve the modelling of R&D and innovation policies both from a conceptual and empirical perspective.
Keywords: C68; D24; D58; H50; O31; O32; 330; RHOMOLO; QUEST; GEM-E3; NEMESIS; Macro-Economic Models; General Equilibrium; R&D Policies